"Drugs don't have age limits": The challenge of setting age restrictions for supervised injection facilities. (4th July 2015) - Watson, Tara Marie; Strike, Carol; Kolla, Gillian; Penn, Rebecca; Bayoumi, Ahmed M.
Abstract: Aims : People under age 18 who inject drugs represent a population at risk of health and social harms. Age restrictions at harm reduction programmes often formally exclude this population, but the reason behind such restrictions is lacking in the literature. To help fill this gap, we examine the perspectives of people who use drugs and various other stakeholders regarding whether supervised injection facilities (SIFs) should have age restrictions. Methods : Interviews and focus groups were conducted with a total of 95 people who use drugs and 141 other stakeholders (including police, fire and emergency services personnel, other city employees and officials, healthcare providers, residents and business representatives) in two Canadian cities without SIFs. Findings : We highlight the following thematic areas: mixed opinions regarding specific age restrictions; safety as a priority; different experiences and understandings of youth, agency and drug use; and ideas regarding maturity, "help" and other approaches. We note throughout that a familiar vulnerability–agency dichotomy often surfaced in the discussions. Conclusions : This paper contributes new empirical insights regarding youth access to SIFs. We offer considerations that may inform discussions occurring in other jurisdictions debating SIF implementation and may help remove or clarify age-related policies for harm reduction programmes.